Optimization of Papaya Seed Oil Production Process (Carica papaya L.) with Soxhlation Extraction Method using Factorial Design - Salsabila, Salsabila; Broto, R. T. D. Wisnu (Journal of Vocational Studies on Applied Research, 2023)
This study aims to optimize the extraction of papaya seed oil (Carica papaya L.) using a factorial design level 2. Papaya seeds are a significant component of the fruit, comprising approximately 14.3% of the total fruit weight. These seeds contain about 25% vegetable oil, predominantly composed of unsaturated fatty acids, which have the potential to be processed into consumable oil. The extraction method employed is Soxhlet extraction using a non-polar solvent, n-hexane. A factorial design level 23 was utilized to determine the most influential process variables. The variables were considered to the ratio of papaya seed mass to solvent volume (1:7 and 1:11), particle size (10 and 30 mesh), and extraction time (170 and 190 min). Optimization was conducted using the quicker method calculation, where the determination of the largest effect and the largest main effect played a crucial role. The analysis revealed that the ratio of papaya seed mass to solvent volume had the most significant main effect, with an effect value of 0.1217. From the analysis, it was found that the 1:7 ratio produced the lowest level of Free Fatty Acids (FFA) in the oil, at 0.5076%, which aligns with the Indonesian National Standard (SNI) requirement of 0.36-0.82% FFA content. Furthermore, an analysis of density, viscosity, and moisture content was conducted on the 1:7 ratio. The test results showed that the 1:7 ratio resulted in an oil density of 0.924 g/mL, moisture content of 0.07127%, and FFA content of 0.5076%. However, based on theoretical knowledge, an increase in FFA content leads to a decrease in oil quality. Additionally, higher ratios corresponded to increased moisture content and density. In conclusion, the papaya seed oil produced in this study complies with the Indonesian National Standard (SNI, 01-3555-1998) regarding FFA content (0.36-0.82%), moisture content (maximum 0.15%), and density (0.924-0.929 g/mL).